REVIEWS (New blackfriars, 1971)
Review in this Article WORDS ABOUT GOD: THE PHILOSOPHY OF RELIGION, edited by Ian T. Ramsey. ST THOMAS AQUINAS: SUMMA THEOLOGIAE. Vol. XVIII: Psychology of Human Acts (la llse vi-xvii), Thomas Gilby, O.P. ALIVE TO GOD. Muslim and Christian Prayer. Compiled with introduction by Kenneth Cragg. DER MENSCHLICHE MENSCH: KARL MARX' JÜDISCHER HUMANISMUS, by Albert Massiczek. INITIATION Ä KARL MARX, by P.-D. Dognin, Editions du Cerf, Paris 1970. BROTHERS IN HOPE (The Bridge, Volume 5), edited by John M. Oesterreicher. BUDDHISM—A NON-THEISTIC RELIGION, by Helmuth von Glasenapp. THE MIND OF CHESTERTON, by Christopher Hollis. LETTERS TO HIS FAMILY, 1901-1962, by Pope John XXIII. VOM JUNGEN ANGELO RONCALLI (1903-1907) ZUM PAPST JOHANNES XXIII (1958-1963), by F. M. William. THE DESTRUCTION OF THE KINGDOM, by H. Gaubert (THE BIBLE IN HISTORY, edited by J. Rhymer, Vol. 6). MAN'S CONCERN WITH HOLINESS, edited by Narina Chavchavadze. L'ESPRIT SAINT DANS LA TRADITION ORTHODOXE, by P. Evdokimov. CREATIVE IMAGINATION IN THE SÜFISM OF IBN ‘ARAB, by Henry Corbin.